Traditional Medicine Utilisation Among Pregnant Women in Sub-saharan African Countries: A Systematic Review of Literature - Nicholas Mudonhi; Wilfred N. Nunu (SAGE Publishing, 2022)
Traditional medicine has the potential to boost the health and economies of many SSA countries, especially if regulatory mechanisms are deployed to govern their protection and utilisation. There is lack of knowledge regarding traditional medicines and their impact on pregnancy. This paper reviews the literature on traditional medicine utilisation among pregnant women in Sub-Saharan African countries. The paper, determined the proportion of pregnant women utilising traditional medicines in Sub-Saharan Africa, identified the different types of traditional medicine used during antenatal care and reasons for Use in Sub-Saharan Africa and also identified challenges that are faced by women who use traditional medicine in antenatal care. A systematic exploratory review was conducted guided by the PRISMA framework. The databases that were searched included Google Scholar, PubMed, Cochrane, HINARI and the World Health Organization. Forty-one literature sources were eligible and included in the review process. Reported traditional medicine utilisation ranged between 12 and 93% among pregnant women in Sub-Saharan Africa. Different types of traditional medicines have been utilised in Sub-Saharan Africa for different purposes. Safety and poor management of usage were reported to be some of the challenges associated with traditional medicine. There is a need to determine chemical components and mode of action of these herbs as some could be beneficial, whilst others harmful, leading to severe pregnancy complications.